2016
DOI: 10.1177/0962280216675373
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genomic signatures for treatment selection with Bayesian predictive failure time models

Abstract: Over the past decade, a tremendous amount of resources have been dedicated to the pursuit of developing genomic signatures that effectively match patients with targeted therapies. Although dozens of therapies that target DNA mutations have been developed, the practice of studying single candidate genes has limited our understanding of cancer. Moreover, many studies of multiple-gene signatures have been conducted for the purpose of identifying prognostic risk cohorts, and thus are limited for selecting personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…Alternatively, we may investigate signatures that have been reported in the literature from different studies. For example, Ma et al (2017) investigated several literature-reported genomic signatures for patients with lung squamous cell carcinoma, and they found that a 13-gene signature developed by (Kaufman et al, 2014) performed well for treatment selection. Thus, the approach is encouraging given that results obtained from these signatures are generally robust due to the external cross validation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, we may investigate signatures that have been reported in the literature from different studies. For example, Ma et al (2017) investigated several literature-reported genomic signatures for patients with lung squamous cell carcinoma, and they found that a 13-gene signature developed by (Kaufman et al, 2014) performed well for treatment selection. Thus, the approach is encouraging given that results obtained from these signatures are generally robust due to the external cross validation process.…”
Section: Discussionmentioning
confidence: 99%
“…We use 0S(i,i)1 to denote the specific pairwise similarity metric between new patient i and the i th patient. Then assume that S(i,i) determines the degree of influence imposed by i th patient in estimating the effectiveness of the treatment received for the new patient, which can be achieved via a power prior model (Ibrahim, Chen, & Sinha, ; Ma et al., , ). Let nj represent the number of previous treated patients receiving treatment j .…”
Section: Bayesian Predictive Methodology For Treatment Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The low success rate is likely the result of ineffective agents as well as the reliance on trial designs that are inadequate for characterizing treatment benefit 5 among predictive subpopulations, inaccurate thresholds for defining molecular subtypes, and analytical approaches that fail to characterize selection rules based on the joint effects of multiple candidate biomarkers. 6–9…”
Section: Introductionmentioning
confidence: 99%
“…4 The low success rate is likely the result of ineffective agents as well as the reliance on trial designs that are inadequate for characterizing treatment benefit 5 among predictive subpopulations, inaccurate thresholds for defining molecular subtypes, and analytical approaches that fail to characterize selection rules based on the joint effects of multiple candidate biomarkers. [6][7][8][9] With the recent focus on precision medicine, exploratory studies should be devised to test the reproducibility of candidate biomarkers as well as identify selection rules that delineate patient subpopulations most likely to benefit from biomarker-guided therapies. The effectiveness with which a treatment's utility to a given type of tumor/patient may be inferred from data inherently depends upon the effectiveness with which the design and method of analysis characterize determinants that are predictive of treatment effectiveness from those that are prognostic, or describe the disease extent.…”
Section: Introductionmentioning
confidence: 99%